LITERASI PEMBIAYAAN, MANAJEMEN USAHA, DAN DIGITALISASI OLEH UMKM MALL NIPAH KOTA MAKASSAR DALAM MENGHADAPI PERSAINGAN PASAR - Marsyanda; Nasrullah; Japar, Rahayu (STKIP Subang, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in driving economic growth; however, they still face various challenges such as low financing literacy, weak business management, and limited utilization of digital technology. This study aims to analyze the effect of financing literacy, business management, and digitalization on the ability of MSMEs to face market competition among MSME actors at Mall Nipah Makassar. This research uses a quantitative method with an associative approach. Data were collected through questionnaires distributed to 50 MSME actors operating at Mall Nipah. Data analysis was conducted using PLS-SEM with SmartPLS 4. The results show that financing literacy (p=0.466) and digitalization (p=0.060) do not have a significant effect on the ability of MSMEs to face market competition, while business management (p=0.022) has a positive and significant effect. The R-square value of 0.378 indicates that 37.8% of the variation in market competition can be explained by the three variables. These findings indicate that effective business management is the most dominant factor in improving MSME competitiveness, while financing literacy and digitalization still need to be improved for optimal impact.